Constitutional guarantee and cosmopolitanism in post-pandemic times. Prospects and challenges - Mesa León, Antonio (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2023)
The global health crisis has given rise a fertile legal-philosophical debate on the protection of human rights. The new scenario calls for new responses from legal philosophy. This paper criticises Luigi Ferrajoli's theory of constitutional guarantee, questioning its suitability as a framework for addressing these challenges. The critique focuses on Ferrajoli's conception of democracy and its cosmopolitan projection. It will be argued that the extension of constitutionalism beyond the state must be based on a gradual and realistic cosmopolitanism.
Keywords: constitutionalism; cosmopolitanism; human rights; guarantee; pandemic